2023
DOI: 10.3389/fimmu.2023.1196931
|View full text |Cite
|
Sign up to set email alerts
|

Targeting transcription factors for therapeutic benefit in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a destructive inflammatory autoimmune disease that causes pain and disability. Many of the currently available drugs for treating RA patients are aimed at halting the progression of the disease and alleviating inflammation. Further, some of these treatment options have drawbacks, including disease recurrence and adverse effects due to long-term use. These inefficiencies have created a need for a different approach to treating RA. Recently, the focus has shifted to direct targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 183 publications
0
4
0
Order By: Relevance
“…These cytokines induce local and subsequent systemic inflammation and cause the stimulation of osteoclasts, all of which lead to cartilage damage, bone resorption, and the degradation of extracellular matrix. Synoviocytes serve as a reservoir for these inflammatory mediators [7,11,63,64]. TNF-α amplifies inflammation by stimulating synovial fibroblasts, which increases the cellular adhesion of mediators and leukocyte movement, subsequently resulting in joint injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cytokines induce local and subsequent systemic inflammation and cause the stimulation of osteoclasts, all of which lead to cartilage damage, bone resorption, and the degradation of extracellular matrix. Synoviocytes serve as a reservoir for these inflammatory mediators [7,11,63,64]. TNF-α amplifies inflammation by stimulating synovial fibroblasts, which increases the cellular adhesion of mediators and leukocyte movement, subsequently resulting in joint injury.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies are mostly used to reduce joint pain and inflammation and also slow the progression of disease by interfering with immune system signaling to suppress the inflammatory processes that cause joint degeneration. However, these agents are relatively costly and have a number of unfavorable side effects [10,11]. With the increasing need for medications to treat RA, there has been a rise in research interest in understanding the pathophysiology of RA and developing novel treatments.…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 was the foremost target, with the highest GDA score of 0.4. Upregulated expression of STAT1 protein and its phosphorylated form has been studied in RA synoviocytes [52], and its activation in the cell, primarily stimulated by different pro-inflammatory cytokines (IFNγ, IL-2, IL-6, IL-7, and IL-21), has been reported to promote cartilage degradation [53]. To evaluate the effect of E2 treatment on STAT1 activation, we analyzed its protein and mRNA expression and found that E2 treatment significantly downregulated the STAT1 expression compared to the control (Figure 5A,E).…”
Section: Estradiol Alters Stat1 Signaling In Ra Synovial Fibroblast T...mentioning
confidence: 99%
“…This may be relevant to the relationship between the protective effect of IRF1 in OA seen here and the potentially pathogenic role for IRF1 in rheumatoid arthritis. In that setting, IRF1 is known to contribute to the tumor necrosis factor α–driven interferon response and has therefore been considered a potential therapeutic target 13–15 . Although this context should be considered for any translational studies building off the findings of Cho et al, 11 the authors showed that producing IRF1 at high levels in the knee joint of mice by injecting adeno‐associated virus–expressing Irf1 did not lead to inflammation or joint pathology, at least at the investigated time points of four and eight weeks after injection.…”
mentioning
confidence: 98%